2015
DOI: 10.1177/0018726714554663
|View full text |Cite
|
Sign up to set email alerts
|

Fairness, envy, guilt and greed: Building equity considerations into agency theory

Abstract: In this paper we examine the extent to which fairness considerations are salient to senior executives and consider the implications for agency theory, tournament theory, and the design of top-management incentives. We look for patterns in a unique data set of senior executive preferences and seek explanations for these patterns using a model of fairness first advanced by Fehr & Schmidt (1999). We propose a number of amendments to Fehr & Schmidt's model. We challenge some of the standard tenets of agency theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 86 publications
0
13
1
1
Order By: Relevance
“…While previous research has argued that fairness is equally germane to senior executives as it is to other workers (Gomez‐Mejia & Wiseman, ; Wade, O'Reilly, & Pollock, ), researchers have generally not considered these in combination with each other. Importantly, recent research building on behavioral agency theory (Wiseman & Gomez‐Mejia, ) challenges some of the standard tenets of agency theory and tournament theory, demonstrating that equity considerations are important and often overlooked in the executive compensation literature (e.g., Pepper & Gore, ; Pepper, Gosling, & Gore, ). Although we measure firm performance and not perception of fairness per se, our results suggest that horizontal pay dispersion and vertical pay compression could be perceived relatively more fairly in prospectors than in defenders, whereas horizontal pay compression and vertical pay dispersion could be seen as being fairer in defenders than in prospectors.…”
Section: Discussioncontrasting
confidence: 99%
“…While previous research has argued that fairness is equally germane to senior executives as it is to other workers (Gomez‐Mejia & Wiseman, ; Wade, O'Reilly, & Pollock, ), researchers have generally not considered these in combination with each other. Importantly, recent research building on behavioral agency theory (Wiseman & Gomez‐Mejia, ) challenges some of the standard tenets of agency theory and tournament theory, demonstrating that equity considerations are important and often overlooked in the executive compensation literature (e.g., Pepper & Gore, ; Pepper, Gosling, & Gore, ). Although we measure firm performance and not perception of fairness per se, our results suggest that horizontal pay dispersion and vertical pay compression could be perceived relatively more fairly in prospectors than in defenders, whereas horizontal pay compression and vertical pay dispersion could be seen as being fairer in defenders than in prospectors.…”
Section: Discussioncontrasting
confidence: 99%
“…For example, behavioral agency theory reevaluates predictions in view of more realistic assumptions about agent behavior, with particular emphasis on internal governance (Pepper and Gore, ). Researchers have incorporated prospect theory (Martin, Gomez‐Mejia, and Wiseman, ) and equity theory (Pepper, Gosling, and Gore, ) into agency theory predictions about how compensation structures influence managerial behavior. We build on the notion of overlaying cognitive biases onto agency theory prescriptions and extend this approach to external governance mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the corporate failures and public distress over the lucrative compensation have revealed that fairness has not taken into consideration when executive compensation schemes are designed (Chaigneau, 2018;Ferracone, 2010). Fairness is a social and ethical norm and it deals with ‗what is just' and ‗what should be done' (Pepper, Gosling, & Gore, 2015). It includes two approaches: the equality (egalitarian) approach and the equity approach.…”
Section: Introductionmentioning
confidence: 99%